High‐Content Analysis of Cell Migration Dynamics within a Micropatterned Screening Platform. Issue 8 (13th June 2019) - Almeida, Filipe V.; Gammon, Luke; Laly, Ana C.; Pundel, Oscar J.; Bishop, Cleo L.; Connelly, John T.
Abstract: Cell migration is a fundamental biological process that is dynamically regulated by complex interactions between the microenvironment and intrinsic gene expression programs. Here, a high‐throughput cell migration assay is developed using micropatterned and dynamically adhesive polymer brush substrates, which support highly precise and consistent control over cell–matrix interactions within a 96‐well cell culture plate format. This system is combined with automated imaging and quantitation of both cell motility and organization of the F‐actin cytoskeleton for high‐content analysis of cell migration phenotypes. Using this platform to screen a library of 147 epigenetic inhibitors identifies a set of EZH2‐specific compounds that promote cytoskeletal remodeling and accelerates keratinocyte migration through derepression of an epithelial to mesenchymal transition‐like gene expression program. Together, these studies establish the high‐throughput, micropatterned assay as a powerful tool for discovery of novel therapeutic targets and for dissecting complex gene–environment interactions involved in wound repair. Abstract : A high‐content screening platform for studying cell migration dynamics is developed using micropatterning and click chemistry tools, in combination with quantitative image analysis. The application of this system in a compound based screen identifies novel epigenetic mechanisms regulating keratinocyte migration and epithelial to mesenchymal transition.